Plan de implementación de un sistema de gestión según la norma NTC 6001:2008 en una micro empresa prestadora de servicios de bienestar (2016)
This monograph describes the implementation plan of a quality system in a microenterprise of the welfare sector located in the city of Bogotá, based on the requirements of the NTC 6001: 2008 standard. This norm is oriented to small and medium enterprises, and establishes the requirements for the implementation of a quality management system in any economic sector. At present, companies in the welfare services sector have shown high growth due to the great importance of the welfare sector by consumers.